Prevalence of methylmalonic acidemia among newborns and the clinical-suspected population: a meta-analyse. (12th December 2022) - Jin, Lizi; Han, Xueyan; He, Falin; Zhang, Chuanbao
Abstract: Importance: Knowing the scale of rare inborn errors is important for screening and resource allocation. Evidence on the prevalence of methylmalonic acidemia (MMA) among newborns and the clinical-suspected population from large-scale screening programs needs to be systematically synthesized. Objective: To estimate the worldwide prevalence of MMA for newborns and the clinical-suspected population and explore the differences in different regions, periods, and diagnostic technologies. Data sources: MEDLINE, Embase, CRD, Cochrane Library, Scopus, CINAHL, and PROSPERO. Study Selection: All studies reporting the epidemiology characteristics of MMA were selected. Data extraction and synthesis: Characteristics of study, subjects, and epidemiology were extracted, random-effect models were used for meta-analyses. Main outcome and measure: Pooled prevalence of MMA. Results: This study included 111 studies. The pooled prevalence of MMA worldwide was 1.14 per 100, 000 newborns (1516/190, 229, 777 newborns, 95% CI: 0.99–1.29) and 652.11 per 100, 000 clinical-suspected patients (1360/4, 805, 665 clinical-suspected individuals, CI: 544.14–760.07). Asia and Africa got a higher pooled prevalence of MMA. The prevalence of MMA in newborns increased through the years, while that in the clinical-suspected population decreased. Collecting blood ≥ 72 h after birth had a higher pooled prevalence of MMA than collecting during 24 h–72 h after birth. The combining-use of MS/MS and GC/MS had a higher pooled prevalence than the single-use of MS/MS or GC/MS. Prevalence of cbl C, mut, cbl B, cbl A, isolated MMA, combined MMA and homocystinuria, vitamin B12-responsive MMA was synthesized. Conclusions and relevance: Prevalence of MMA among newborns was extremely low, but considerably high in the clinical-suspected population, indicating the need for more efficient newborn screening strategies and closer monitoring of the high-risk population for the early signs of MMA. Asia and Africa should attach importance to the high prevalence of MMA. Further diagnostic tests were recommended for the combining-use vs single-use of MS/MS and GC/MS and for collecting blood after 72 h vs during 24–72 h after birth.